ChemInform Abstract: Strain‐Promoted Reaction of 1, 2, 4‐Triazines with Bicyclononynes. Issue 9 (February 2016) - Horner, Katherine A.; Valette, Nathalie M.; Webb, Michael E.
Abstract: The inverse electron‐demand Diels—Alder reaction of triazinylalanine (I) with the strained eight‐membered cycloalkyne (II) is investigated as model reaction for late stage protein‐labelling applications.